First principle study of structural and electronic properties of cubic quaternary BxGa1−xAs1−yNy alloys. (March 2015) - Abdiche, A.; Riane, R.; Guemou, M.; Khenata, R.; Moussa, R.; Murtaza, G.; Bin Omran, S.
Abstract: In this paper, we have studied the structural and electronic properties of GaAs, GaN, BN, BAs binary compounds and their ternary and quaternary solid solutions using the full potential-linearized augmented plane wave method within density functional theory. We have used the generalized gradient approximation GGA that is based on exchange-correlation energy optimization for calculating the total energy. Moreover, the local density approximation LDA is also applied. Furthermore, the effect of composition on lattice constant, bulk modulus and band gap for binary compounds as well as for quaternary alloys have been studied which showed nonlinear dependence on the composition. The bowing of the fundamental gap versus composition predicted by our calculations is in very good agreement with experiments available for binary alloys. In addition, the energy band gap of zincblende B x Ga1− x As1− y N y quaternary alloys lattice matched to BAs substrate is investigated. It should be noted that the present work is the first theoretical study of the quaternary alloys of interest and still awaits experimental confirmations. Highlights: We have investigated the combined effect of the insertion of boron and nitride into GaAs, in order to modulate the band gap. The band gap variations is significant. The combined incorporation of boron and nitride into GaAs enlarge the possibilities of deposition on different substrates. This work is the first one for BGaAsN alloys and may help the future works.